The Theology of The Body as A Pastoral Approach to Preventing Juvenile Delinquency - Dominikus Doni Ola; Risni Karina Bu'ulolo; Evimawati Harefa; Megawati Naibaho; Yusuf Nataeli Lase (Al-Albab, 2025)
Theology of the Body is a theological and philosophical reflection that seeks to help adolescents understand their identity as human persons created in the image and likeness of God. This study aims to examine the Theology of the Body and deepen understanding of the meaning of the human body and the value of human dignity in adolescent life, based on the teachings of Pope John Paul II. The method used is library research, involving the collection of relevant literature, critical reading, and the analysis of academic sources. The findings suggest that a comprehensive understanding of the Theology of the Body can foster a greater respect for the dignity of the human person and an increased awareness of the purpose of creation. In practical terms, these insights may be applied through character education programs rooted in the spirituality of the body within Catholic schools, pastoral accompaniment for adolescents that emphasizes the body as a gift, and the development of catechetical modules that integrate Theology of the Body with contemporary issues such as pornography, premarital sex, and identity crises. The scholarly contribution of this study lies in its formation of a theoretical framework that supports further development in the fields of theology, philosophy, and moral education for youth. Moreover, this study provides space for interdisciplinary dialogue between theology and the social sciences in addressing the complexity of juvenile delinquency in a more holistic and contextualized manner.